Monitoring Compressive Strength Development of Mortar Using Cement-Based Piezoelectric Composite Under Low Electric Field Polarization - Gati Annisa Hayu; Wahyuniarsih Sutrisno; Kiki Dwi Wulandari; Priyo Suprobo (Salehan Institute of Higher Education, 2026)
The Cement-based Piezoelectric Composite (CPC) used in this research is a 0-3 type, composed of Lead Zirconate Titanate (PZT) powder and cement with a 50:50 volume ratio. The CPC was produced under low electric field polarization with specific durations: C1 (250 V/mm, 40 minutes), C2 (250 V/mm, 60 minutes), C3 (375 V/mm, 40 minutes), and C4 (375 V/mm, 60 minutes). CPC was embedded inside the mortar to monitor the strength development for 90 days using the Electromechanical Impedance (EMI) technique. The results show that the conductance decreases (resistance increases) as the compressive strength increases. A more thorough analysis was conducted using the Root Mean Square Deviation (RMSD) technique, which serves as an effective indicator of concrete strength development and damage. This analysis aims to establish a quantitative correlation between the sensor's conductance and the mortar's strength as it develops. The results show that the increase in compressive strength corresponds with an increase in conductance RMSD, which indicates the sensor sensitivity. Furthermore, the C4 sample exhibits the greatest sensitivity and capability for monitoring the development of compressive strength. Even though the d33 values are relatively low, at 4.87 pC/N, C4 can detect the compressive strength up to 90 days with a broad frequency range of 300-1000 kHz. CPC with low electric field polarization can still be utilized as an embedded sensor to monitor the development of compressive strength in cementitious materials.